Independent Road Corridor as a Cultural Reservation Area in the Old Town of Tanjungpinang - Malinda Budiati; Yuanita FD Sidabutar; Gunawan Toto Hadi (Budapest International Research and Critics University, 2022)
The development of a large city which also functions as the Capital of the Province and its residents is a symbiosis that is interrelated and influences each other. Changes, developments, and urban growth require the provision of new space, facilities and infrastructure so that as an implication there is a change and growth of buildings and their facilities and infrastructure. One of the urban space systems in Tanjungpinang that needs serious attention and arrangement is the Kota Lama area. This area is one of the tourist attractions visited by many domestic and foreign tourists and is the busiest major trading area. The Old City area is a Cultural Conservation Area, Environmental conditions around the area at this time tend to grow irregularly and sporadically in line with the rapid development of physical development in the area. It is necessary to anticipate the possibility of a decrease in environmental quality. If this is not anticipated immediately through intensive control, it is feared that there will be irregularities in the function and role of regional space in the future.